Comparison of traffic assignment in VISUM and transport simulation in MATSim - Bartłomiej PIĄTKOWSKI; Michał MACIEJEWSKI (Transport Problems, 2013)
The paper presents a comparison of different approaches to traffic modelling and forecasting in VISUM and MATSim. The comparison was based on three indicators: link volumes, average travel time and distance. For this purpose, a virtual city with a road network and an OD matrix describing travel demands were created. Next the input data were created to both systems. The equilibrium and the dynamic stochastic assignment algorithms were used in VISUM while in MATSim a multi-agent approach was used for planning and a queue-based flow model for simulation. The comparison showed that although the overall results obtained in both systems were convergent, the detailed distribution of traffic was different. In VISUM the static assignment algorithm resulted in increased traffic flow on links located near to the connectors, while the dynamic one assigned traffic more uniformly, matching the MATSim’s results.